Physiological Mechanisms of Improved Smut Resistance in Sugarcane Through Application of Silicon - Deng, Quanqing; Wu, Jia; Chen, Jianwen; Shen, Wankuan (Frontiers in Plant Science, 2020)
Sugarcane smut caused by Sporisorium scitamineum is a severe, global sugarcane disease with severe economic losses and is difficult to prevent. To explore more effective control techniques for smut, the effects and physiological mechanism of silicon (Si) on smut resistance in two smut-susceptible cultivars, ROC22 and Badila, were investigated. The results show that Si application significantly enhances smut resistance in ROC22 and Badila, and the incidence of sugarcane smut decreased by 11.57–22.58% (ROC22) and 27.75–46.67% (Badila). The incidence of smut is negatively correlated with the amount of Si applied and the Si content in sugarcane leaves, stems, and roots (highly significantly negatively correlated with stem Si content). Under S. scitamineum stress, the activities of pathogenesis-related enzymes, chitinase and β-1,3-glucanase, secondary metabolism-related enzymes such as polyphenoloxidase (PPO) and phenylalanine-ammonia-lyase (PAL), and the contents of secondary metabolites, total soluble phenol, and lignin in sugarcane leaves treated with Si were significantly higher than those without Si (CK). The results also demonstrated that the content of malondialdehyde (MDA) and hydrogen peroxide (H2O2), the superoxide dismutase (SOD) activity of sugarcane leaves treated with Si increased in the seedling and tillering stages, and the peroxidase (POD) activity decreased in the seedling stage, which caused the accumulation of reactive oxygen species (ROS) that in turn triggered defense responses. Moreover, MDA and H2O2 levels decreased, and the activities of SOD and POD increased at the jointing stage, which was beneficial to the removal of excessive ROS. Collectively, these results suggest that Si modulates pathogenesis-related protein activity, secondary metabolism, and active oxygen metabolism of sugarcane that positively regulate resistance to smut. This study is the first to reveal the physiological mechanism of Si in improving smut resistance in sugarcane, and the results provide a theoretical basis for the development of Si fertilizers to control sugarcane smut.